Reliability and failure analysis of high-power led packaging. - Tan, Cher Ming (Woodhead Publishing series in electronic and optical materials, 2022)
Reliability and Failure Analysis of High-Power LED Packaging provides fundamental understanding of the reliability and failure analysis of materials for high-power LED packaging, with the ultimate goal of enabling new packaging materials. This book describes the limitations of the present reliability standards in determining the lifetime of high-power LEDs due to the lack of deep understanding of the packaging materials and their interaction with each other. Many new failure mechanisms are investigated and presented with consideration of the different stresses imposed by varying environmental conditions. The detailed failure mechanisms are unique to this book and will provide insights for readers regarding the possible failure mechanisms in high-power LEDs. The authors also show the importance of simulation in understanding the hidden failure mechanisms in LEDs. Along with simulation, the use of various destructive and non-destructive tools such as C-SAM, SEM, FTIR, Optical Microscopy, etc. in investigation of the causes of LED failures are reviewed. The advancement of LEDs in the last two decades has opened vast new applications for LEDs which also has led to harsher stress conditions for high-power LEDs. Thus, existing standards and reliability tests need to be revised to meet the new demands for high-power LEDs.